The effect of a spectral filter on visual quality in patients with an extended-depth-of-focus intraocular lens - Łabuz, Grzegorz; Auffarth, Gerd U.; Özen, Aydin; Berg, Thomas J. T. P. van den; Yildirim, Timur Mert; Son, Hyeck Soo; Khoramnia, Ramin (American journal of ophthalmology, 2019)
Purpose - Wavelength dependence of diffractive intraocular lenses (IOLs) was recognized in vitro but not yet assessed in vivo. By examining pseudophakic patients who had extended-depth-of-focus diffractive implants, this spectral effect on their vision was measured clinically and the lens was tested in vitro. - Design - Cross-sectional study with laboratory investigation. - Methods - Twelve pseudophakic patients (23 eyes) with a Symfony lens (Johnson & Johnson Vision) were measured monocularly under red and white light at far, intermediate, and near distances. Corrected distance visual acuity (CDVA), distance-corrected intermediate visual acuity (DCIVA), and distance corrected near visual acuity (DCNVA) were assessed. Contrast sensitivity was examined at several spatial frequencies. The in vitro lens modulation transfer function was measured under different spectral conditions by using an IOL metrology device. - Results - CDVA was comparable under red and white light. DCIVA and DCNVA were significantly better under white light by 0.06 and 0.09, respectively. Contrast sensitivity was slightly better with a red filter at far distance but was worse at intermediate distance, although differences were significant only at 1 frequency. Near contrast sensitivity was better under polychromatic than red light, which was significant at 3 frequencies. The in vitro analysis confirmed Symfony's wavelength dependence: performance was improved at far distance but was worse at intermediate and near distances. - Conclusions - Symfony's spectral dependence was observed to affect visual acuity and contrast sensitivity. Although the red filter did not improve distance vision, it caused visual deterioration at near distance. One should take this effect into account when optimizing the reading performance of patients with diffractive IOLs.